Enacting knowledge exchange: a context dependent and 'role-based' typology for capturing utility from university research. (1st March 2015) - Vico, Eugenia Perez; Hellsmark, Hans; Jacob, Merle
Abstract : One of the key research and policy problems in innovation studies is the development of tools for understanding and measuring the impact of academic research on society. The paper contributes to resolving this problem by providing a typology that helps us to understand and analyse the roles researchers take on in order to make academic knowledge useful. A key finding is that utility creation is context dependent and varies between individual researchers and research groups. Attempts to measure impact ought therefore to allow for diversity with regard to the individual researcher or research group in the context of knowledge creation.